Efficacy and safety of nebulized drugs in the treatment of non-severe mycoplasma pneumoniae pneumonia in children - a network meta-analysis - Zeng, Li; Ye, Hanlin; Zhang, Qiu; Xu, Ting; Xu, Hong; Bi, Dan (Frontiers in Pharmacology, 2025)
ObjectiveTo systematically evaluate the efficacy and safety of commonly used nebulized drugs as adjuvant treatment for non-severe mycoplasma pneumoniae pneumonia (MPP) in children, providing an evidence-based reference for clinical medication.MethodsA computerized search of major Chinese and English literature databases was conducted to collect randomized controlled trials (RCTs) that utilized nebulized drugs in conjunction with azithromycin (AZM) or AZM alone in children with MPP. Following literature screening, the quality of the included studies was evaluated using the risk of bias assessment tool as recommended by the Cochrane Handbook. Outcome data for each measurement were extracted, and a network meta-analysis was conducted using Stata 17.0.ResultsA total of 79 RCTs involving 7,712 patients and 9 interventions were included. The network meta-analysis indicated that all nebulized drugs combined with AZM markedly improved clinical efficacy compared to AZM alone. Among these, the combination of nebulized budesonide plus terbutaline demonstrated superior efficacy and safety as adjunctive therapy for non-severe MPP. Furthermore, Ambroxol combined with AZM was particularly effective in shortening the duration of clinical symptoms such as fever and lung rales. The combinations of terbutaline or budesonide with AZM significantly improved pulmonary function.ConclusionNebulized drug adjuvants to AZM therapy enhance treatment efficacy in children with non-severe MPP without increasing the incidence of adverse events. However, there is a need for more extensive, higher-quality clinical studies to overcome the limitations due to the low quality of some included articles.